Integrating Turkey’s renewable energy with global carbon market - Göncü, Hasan Ali. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2010., 2010)
Climate change is recognized as one of the major problems of the globe and unless appropriate measures are taken it is likely to result in irreparable damages on the planet in the near future. Electricity energy is at the heart of this problem and so must be an important player in the solution. Turkey’s electricity energy market has recently entered into transition period and if properly managed, Turkey’s highly problematic electricity energy market may prosper. Turkey’s electricity energy sector is currently characterized by low supply security, high carbon intensivity and high costs. After examining global and Turkey’s electricity energy outlook in details, this sudy offers a solution to transform Turkey’s electricity energy sector into a low-cost, environment-friendly and reliable structure. Wind power is a candidate to play the key role when Turkey’s immense untapped wind power potential is considered. Increasing global concern for climate change and the EU regulations are expected to force Turkey to recognize the importance of greenhouse gas (GHG) emissions in investment decisions in the near future. With extensive analysis on the regulated carbon markets and voluntary carbon markets, this study may serve as a roadmap for Turkey to take the right action in the global climate change negotiations. In addition, this study may serve as a guideline for wind power project developers in exploring the opportunities in the global carbon market.
Keywords: Renewable energy -- Turkey.